Association Between Maternal Body Mass Index During Pregnancy, Short-term Morbidity, and Increased Health Service Costs: A Population-based Study. Issue 1 (March 2015) - Denison, F.C.; Norwood, P.; Bhattacharya, S.; Duffy, A.; Mahmood, T.; Morris, C.; Raja, E.A.; Norman, J.E.; Lee, A.J.; Scotland, G.
Abstract : ( BJOG . 2014;121(1):72–81)